Pemanfaatan Aplikasi CorelDRAW Sebagai Media Pembelajaran Pada Siswa Jurusan Manajemen Mengenai Advertising Desain - Dedi Leman; Cindy Paramitha Lubis; Hari Ramadhan; Muhamad Rizky Fajar Utomo (Unity Academy, 2024)
The Corel Draw application as a learning medium aims to support students' creative spirit. The use of CorelDRAW is able to support student creativity by acting as a means for expressing creative ideas, as well as arousing curiosity so that students' creativity continues to develop while carrying out independent learning activities. Good for management students who use the CorelDRAW application as advertising design media (advertising promotion design). The Corel Draw application can be used as an indispensable medium for every student, both independently and for college assignments. The method used is a literature study by reviewing 11 journals and 2 theses that are most relevant to the research topic. CorelDRAW was chosen because it has tools for creating vector objects, drawing illustrations, manipulating bitmap images, giving effects, and creating and creating text. With these capabilities, CorelDRAW is considered a suitable medium for students to use to support creativity in their independent learning activities. The research results show that the use of CorelDRAW can increase student creativity. This is proven by the benefits students get after mastering the CorelDRAW application